2016
DOI: 10.1530/eje-16-0105
|View full text |Cite
|
Sign up to set email alerts
|

Cut-off limits of the peak GH response to stimulation tests for the diagnosis of GH deficiency in children and adolescents: study in patients with organic GHD

Abstract: Objective: The diagnosis of GH deficiency (GHD) in children and adolescents is established when GH concentrations fail to reach an arbitrary cut-off level after at least two provocative tests. The objective of the study was to define the optimal GH cut-offs to provocative tests in children and adolescents. Design: Retrospective study in 372 subjects who underwent evaluation of GH secretion. GH and IGF-I were measured by chemiluminescence assay in all samples. Receiver operating characteristic (ROC) analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 39 publications
(47 reference statements)
2
42
0
5
Order By: Relevance
“…Not surprisingly, mean IGF‐I concentrations were significantly lower in the prepubertal and pubertal GHD children, although with overlapping values. These data are in accordance with our previous studies showing that, despite IGF‐I alone is characterized by a low diagnostic accuracy, it is useful in combination with the results of GH stimulation testing and increases the diagnostic accuracy of the latter …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Not surprisingly, mean IGF‐I concentrations were significantly lower in the prepubertal and pubertal GHD children, although with overlapping values. These data are in accordance with our previous studies showing that, despite IGF‐I alone is characterized by a low diagnostic accuracy, it is useful in combination with the results of GH stimulation testing and increases the diagnostic accuracy of the latter …”
Section: Discussionsupporting
confidence: 93%
“…Although current guidelines still indicate a cut‐off of 10 μg/L, this value is not supported by robust clinical data. We have recently shown that the best cut‐off for GH peak after CT, measured by chemiluminescent immunometric assay, is 6.8 μg/L, with an efficiency of 96.3% . In this study, we found that when applying a cut‐off of 7 μg/L, 11 subjects (six prepubertal and five pubertal) failed CT but showed normal GH responses to a second stimulation test, yielding an overall false positive responses rate of 3.3%.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations